Kathy Acker writing the impossible - Colby, Georgina (Edinburgh University Press, 2016)
An in-depth analysis of the work of one of the twentieth century's most innovative writers. Kathy Acker's body of work is one of the most significant collections of experimental writing in English. In Kathy Acker: Writing the Impossible, Georgina Colby explores Acker's compositional processes and intricate experimental practices, from early poetic exercises written in the 1970s to her final writings in 1997. Through original archival research, Colby traces the stages in Acker's writing and draws on her knowledge of unpublished manuscripts, notebooks, essays, illustrations, and correspondence to produce new ways of reading Acker's works. Rather than treating Acker as a postmodern writer this book argues that Acker continued a radical modernist engagement with the crisis of language, and carried out a series of experiments in composition and writing that are comparable in scope and rigor to her modernist predecessors Stein and Joyce. Each chapter focuses on a particular compositional method and insists on the importance of avant-garde experiment to the process of making new non-conventional modes of meaning. Combining close attention to the form of Acker's experimental writings with a consideration of the literary cultures from which she emerged, Colby positions Acker as a key figure in the American avant-garde, and a pioneer of contemporary experimental women's writing. Key Features Examines unpublished manuscripts, notebooks, lecture notes, letters and manuscripts from the Kathy Acker Papers Features eleven previously unpublished images of original manuscripts, correspondence, and colour illustrations from the Kathy Acker Papers Utilises major archival study of Acker's experimental compositional practices Situates Acker as a late modernist writer and a key figure in the American Avant-Garde
Title from publisher's bibliographic system (viewed on 10 May 2017)
Writing asystematically : early experimental writings 1970-1979 -- Collage and the anxiety of self-description ; Blood and Guts in high school -- Writing-through : Don Quixote ; which was a dream -- Intertextuality and constructive non-identity : in Memoriam to Identity -- Montage and creative cutting : my mother -- Ekphrasis, abstraction, and myth : 'from psyche's journal', Eurydice in the underworld, 'Requiem'
Keywords: Acker, Kathy / 1948-1997 / Criticism and interpretation; Acker, Kathy -- 1948-1997